Twitter Time : A Temporal Analysis of Tweet Streams During Televised Political Debate - Pond, Philip (Television & New Media, 2016)
This article examines the role that the microblogging service Twitter plays in engaging audiences with televised political debate. Analysis focuses on Q&A, a political discussion show hosted by the Australian Broadcasting Corporation, and the #QandA hashtag used to discuss the broadcast. Analysis suggests that rather than enabling user-to-user communication, the #QandA stream is characterized by the struggle to signify and complex nonlinear temporalities. These contributions to ongoing language wars imply an emergent type of audience engagement, which may not be compatible with a normative framing of deliberative discourse.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xNTI3NDc2NDE1NjE2MTkw